The Effect of Shopping Emotion and Trust in NCT Merchandise Purchase Decisions at X in Surabaya - Nurul Aulia Dewi; Zumrotul Fitriyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to determine the influence of shopping emotion and trust on NCT merchandise purchase decisions on X at NCTZen Surabaya. This research was carried out because the development of social media is no longer used for communication, but can be used for promotional media. Digital marketing can be done on social media, one of which is X. This research is expected to be a reference for future literature. The method used in this study uses PLS with a quantitative approach with a purposive sampling method using a Likert scale. The questionnaire consisted of 90 respondents with the criteria of NCT fans in Surabaya and had purchased NCT merchandise on X. The results of this study show that shopping emotion and trust have an influence and contribute to purchase decisions.